Analisis Penerapan Artificial Intelligence terhadap Efektivitas Social Media Marketing pada Akun Instagram Cuci Sepatu Kelen dengan Pendekatan Model AIDA - Muhammad Ikhsan Ali; Nur Ahmadi Bi Rahmani; Nurwani Nurwani (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
This research aims to examine the application, obstacles and benefits of Artificial Intelligence ChatGPT on the effectiveness of social media marketing using the Attention, Interest, Desire, Action (AIDA) model approach, especially on the Cuci Shoes Kelen Instagram account. The background to this research is the Industrial Revolution 4.0 which has created an era of digital technology with a high number of internet users in Indonesia, even though digital understanding and literacy is still low. This research uses descriptive qualitative methods by collecting data through virtual ethnography and interviews. The research subjects consisted of two owners of "Cuci Shoes Kelen," namely DB and FP, while the research object was the use of Artificial Intelligence ChatGPT in this account. The results of the first research showed that the application of Artificial Intelligence ChatGPT with the AIDA model approach on the Instagram account "Cuci Shoes Kelen" resulted in improvements in all aspects measured. Therefore, the marketing and promotional content produced by ChatGPT can increase the effectiveness of social media marketing. The results of the second research show that there are obstacles in implementing ChatGPT Artificial Intelligence, especially in new users' understanding of the types of questions that should be asked to ChatGPT, and also the limited information in ChatGPT version 3.5. However, benefits include ChatGPT's ability to provide promotional strategy recommendations that comply with AIDA concepts and detailed guidance for their implementation.